The Effectiveness of Online Learning Based on The Complete Sentence Model on Student Learning Outcomes on Theme 2 Sub-Theme 1 in Second Grade Writing Skills - Asri, Reni; Kiswoyo, Kiswoyo; Fajriyah, Khusnul (Universitas Pendidikan Ganesha, 2021)
Children's language skills are a problem that needs attention because many children are not yet able to write and use good and correct language. The purpose of this study was to analyze the effectiveness of online learning based on the complete sentence model on student learning outcomes in Theme 2 Playing in My Environment Sub-theme 1 Playing in the Home environment writing skills for class II. This type of research is experimental research with a research design that is pre-experimental designs. The study population was class II consisting of 28 students for the 2020-2021 school year. The sample taken was class II students consisting of 28 students using nonprobability sampling techniques. In this study, the data analysis technique used is quantitative statistical data analysis techniques. The results showed that the score of the t-test showed that the results of the calculation of the score data of students with t count = 1.717804 with a price of t table = 1.701113, then t count> t table. This research concludes that there is a significant increase, so online learning based on the complete sentence model is effectively used for student learning outcomes in theme 2 Playing in My Environment Sub-theme 1 Playing in the Home environment writing skills class II.